The Effect Of Force Majeure On The Implementation Of The Documentary Credit Contract - صارم يونس; عثمان سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2020)
International trade contracts are considered one of the most important topics of international law, because they are reflected on the economies of all countries, and that they are of the successive contracts, where goods take time to cross the borders of more than one country, which makes them exposed to risks. And since the documentary credit is one of the international trade contracts for its role in providing guarantee for the international sales, It is also one of the most capable means that the modern era has known in contributing to the completion of international trade deals, one the most important banking operations in the world, one of the most used tools of payment in international trade, and for its success as a fast-performing and low-cost tool, and since the documentary credit contract has a number of stages until it reaches its goal, this process may be hampered by unexpected events that are independent of the will of the debtor and affect the implementation making it either impossible as force majeure, or exhausting for debtor while remaining possible; as emergency circumstance.